Optimizing The Use of Sharia Digital Transactions to Support Indonesia's Economic Recovery - Alfarizi, Muhammad; Hanum, Rastinia Kamila; H, Syaibatul Aslamiyah (Jurnal Ilmu Ekonomi Terapan, 2021)
The digital economy in Indonesia is experiencing very rapid development, especially in financial technology (fintech). The development of fintech is expected to have an influence on economic growth, whether implemented by conventional or sharia systems, especially during the economy recovery period during COVID-19 . This research was conducted with a quantitative approach with secondary data studies from various related institutions accompanied by a literature review that was relevant to this topic. The results of this study show various facts including not only conventional fintech which is increasingly showing stretching, Islamic fintech is starting to become a growing trend in Indonesia apart from conventional fintech. Even though during the pandemic, sharia fintech services had experienced ups and downs in the period until January 2021, but they showed positive changes with an increase in the percentage or number of graphs. However, there are still many LinkAja customers who have not activated sharia services due to various factors. Various efforts are needed to increase the effectiveness of LinkAja Syariah in the transaction process in order to support Indonesia's economic recovery